“I’m trying to figure out who the hell I am”: Examining the psychosocial and mental health experience of individuals learning “Not Parent Expected” news from a direct-to-consumer DNA ancestry test - Juliette Careau; Maarten H.D. Larmuseau; Rebekah Drumsta; Rob Whitley (BMC Psychiatry)
Abstract Background According to recent estimates, around 30 million people have taken Direct-to-Consumer DNA ancestry tests, typically marketed as a fun, harmless and exciting process of discovery. These tests estimate a user’s ethnic ancestry, also matching users with biological relations on their database. This matching can produce a surprising ‘not parent expected’ discovery, where a user learns that an assumed parent (typically the father) is not a biological parent. Such news may negatively affect mental health, self-identity and familial relationships, while prompting the utilization of putatively helpful resources by affected individuals. However, there is a lack of research on this topic. Thus, this study aimed to document the psychosocial experience of adults who have learnt that an assumed parent is not a biological parent via a Direct-to-Consumer DNA ancestry test. Specific objectives include investigating and understanding impact on mental health, familial relationships and subsequent resources mobilized. Methods To meet these objectives, we conducted an inductive qualitative study, allowing for the documentation of common experiences and perspectives. This involved 52 semi-structured interviews with affected individuals, analyzed using thematic analysis. Results This resulted in five overlapping themes, namely (i) participants typically described their experience as an extraordinary shock that had a negative impact on their mental health, with some exceptions; (ii) the experience typically led to a severe and troubling disruption of their self-identity, with some exceptions; (iii) the news often ruptured extant familial relationships, especially with the mother, and any experiences with the new biological family were mixed; (iv) participants sought support from a variety of resources including spouses, siblings, and online peer support groups, which were generally considered helpful, with some exceptions; and (v) many participants consulted mental health professionals, who were sometimes considered supportive, but some participants noted that they were ill-equipped to help. Common across these themes were issues of grief, loss and trauma. Conclusions This study reveals an expanding, vulnerable, and under-researched population facing unique stressors, that may be at high risk of developing a psychiatric disorder. There is a need for new services and supports for this population including tailored clinical interventions and specific self-care resources.